Analisis Pengangguran Terbuka di Indonesia - Nicko Abdul Rahman; Novya Zulfa Riani (Universitas Negeri Padang, 2023)
The purpose of this research was conducted to analyze: (1) To what extent does the number of people affect open-mindedness in Indonesia, (2) To what extent does education influence open-sensitivity in Indonesia, (3) To what extent does open inequality affect responsiveness in Indonesia, (4) To what extent does population, education and income inequality influence open resistance in Indonesia. This research is a descriptive and inductive type of research. The data used is secondary panel data for 34 provinces in Indonesia from 2017-2021 obtained from related institutions and then analyzed using panel regression models and Random Effect selection models. The results of the study show that simultaneously, the influence of population, education and income inequality has a significant influence on open response in Indonesia. Furthermore, partially (1) population has a positive and insignificant effect on open responses in Indonesia. (2) Education has a positive and significant effect on open response in Indonesia. (3) Inequality has a positive and insignificant effect on open responses in Indonesia.